Aero-thermal performance and enhanced internal cooling of unshrouded turbine blade tips - Virdi, AS (2015)
The tips of unshrouded, high-pressure turbine blades are prone to significantly high heat loads. The gap between the tip and over-tip casing is the root cause of undesirable over-tip leakage flow that is directly responsible for high thermal material degradation and is a major source of aerodynamic loss within a turbine. Both must be minimised for the safe working and improved performance of future gas-turbines. A joint experimental and numerical study is presented to understand and characterise the heat transfer and aerodynamics of unshrouded blade tips. The investigation is undertaken with the use of a squealer or cavity tip design, known for o↵ering the best overall compromise between the tip aerodynamics, heat transfer and mechanical stress. Since there is a lack of understanding of these tips at engine-realistic conditions, the present study comprises of a detailed analysis using a high-speed linear cascade and computational simulations. The aero-thermal performance is studied to provide a better insight into the behaviour of squealer tips, the e↵ects of casing movement and tip cooling. The linear cascade environment has proved beneficial for its o↵ering of spatially-resolved data maps and its ability to validate computational results. Due to the unknown tip gap height within an entire engine cycle, the e↵ects of gap height are assessed. The squealer's aero-thermal performance has been shown to be linked with the gap height, and qualitative different trends in heat transfer are established between low-speed and high-speed tip flow regimes. To the author's knowledge, the present work is the first of its kind, providing comprehensive aero-thermal experimental research and a dataset for a squealer tip at engine-representative transonic conditions. It is also unique in terms of conducting direct and systematic validations of a major industrial computational fluid dynamics method for aero-thermal performance prediction of squealer tips at enginerepresentative transonic conditions. Finally, after recognising the highest heat loads are found on the squealer rims, a novel shaped squealer tip has been investigated to help improve the thermal performance of the squealer with a goal to improve its durability. It has been discovered that a seven percent reduction in tip temperature can be achieved through incorporating a shaped squealer and maximising the internal cooling performance.